Women’s Empowerment and Intra-Household Bargaining Power - Nacka, Marina; Drichoutis, Andreas; Nayga J. Rodolfo (My University, 2024)
We assess the effectiveness of the Abbreviated Women’s Empowerment in Agri culture Index (A-WEAI) in predicting intra-household bargaining power. We con ducted a lab-in-the-field experiment with 464 agricultural households, where spouses made decisions about money allocations. The experiment tested whether they would choose efficient overall household gains or favor individual monetary ben efits. Our findings demonstrate that women’s empowerment levels, as measured by the A-WEAI, are predictive of decisions in the allocation task. This supports the A-WEAI’s utility in representing and predicting intra-household dynamics.
Keywords: A-WEAI, allocation task, dictator game, agricultural households